The Challenges of Education Financing in the Digital Era: A Systematic Literature Review of the Gap in Access and Quality of Education 2015-2024 - Raihan, Izza Mutia; Ahmad, Masduki; Rochimah, Heni (Journal of English Language and Education, 2025)
The digital era has created a paradox in education financing where technology that is supposed to democratize access actually deepens the gap through the digital divide. This research aims to analyze the challenges of education financing in the digital era and its impact on the gap in access and quality of education through a systematic literature review for the period 2015-2024. The research method uses an SLR approach with the PRISMA 2020 protocol, analyzing 10 selected studies from the Scopus, Web of Science, ERIC, and Google Scholar databases. The findings show 65% of low-income students do not have adequate access to technology with a 23% decline in achievement, urban-rural digital financing disparities reach a 3:1 ratio, and an average institutional digital transformation cost of $150,000 with 60% requiring external funding. Alternative financing models such as public-private partnerships can reduce costs by up to 35%, but require contextual adaptation. It is necessary to reconceptualize education financing from a transactional model to a holistic ecosystem investment to ensure sustainable access to quality education in the digital era.